Specific gravity value of cement for concrete design - Obando-Angulo, Victor Manrique (2023)
Generally, when a concrete mix is designed, the value of the cement specific weight is used to convert volumes to weights and the other way around. For cement, the standard value of this parameter is generally accepted in 3.18, but studies indicate that this value is highly variable depending on the cement composition. In this article, the experimental results obtained by designing the concrete JMF under the ACI-211.1-91 methodology was analyzed, using mixed cements such as MM/B(P-C)-28, which has additions of pozzolans, limestone and gypsum. The methodology is based on pure cements with clinker factors of up to 95%, which in the case of the cement used, has a value between 65% and 79%. Based on the proposed experimental scheme, it was possible to determine that the specific weight of the cement varies according to their composition, which is directly linked to their addictions. In this case, it was concluded that for a concrete mix design, the value of this parameter must always be verified, since when passing from weights to volumes, the value can greatly affect the required proportions of cement. In general the parameter is accepted as 3.18 but it varies significantly according to the type of cement: for example in cement type MM/C (P-C)-28 this value is 2.81. The previous means that when converting 100 m3 of concrete from mass to volume, an overdosage of up to 100 bags of cement can occur, which in turn increases costs and causes problems such as over-rigidity and high hydration heat.